Síntese de conjugados e nanopartículas auto-organizadas de goma do cajueiro oxidada e anfotericina B - Rodrigues, Nadia Aline de Oliveira Pitombeira (2019)
Leishmaniasis is a zoonotic infectious disease of cutaneous or visceral manifestation, distributed worldwide, which affects humans and animals. In Brazil the drug of first choice for leishmaniasis treatment are pentavalent antimony (Sb+5), an example is the methylglucamine antimoniate (Glucantime®). Amphotericin B (AmB) is the second choice drug and it is used when a satisfactory response to treatment with pentavalent antimonial is not obtained. The aim of this work is to prepare conjugates of oxidate cashew gum (OCG) and AmB via Schiff base formation to provide greater solubility and decrease AmB toxicity. Nanoparticles of the conjugate were also prepared by self-organization and its size and zeta potential were obtained. The gum cashew (GC) was oxidized with sodium periodate to produce aldehyde groups on the polysaccharide chain. The content of oxidized hydroxyl groups to aldehyde groups was 20 and 50% respectively for the CGO20 and CGO50 samples. The yield of the oxidation reaction was 91.3% for the GCO 20% and 75.7% for the GCO 50%. The oxidized derivatives were characterized by infrared spectroscopy and thermal gravimetric analysis. The conjugates of the oxidized samples with AmB were obtained in a yield of 84.5 and 61.6% and the content of AmB was 4.9 and 24.8% respectively for the GCO20-AmB GCO50-AmB samples. The conjugates show a yellowish color characteristic of AmB and infrared and UV-Vis spectra confirm the insertion of AmB. The solubility of the conjugates was 3.3 mg /mL and 0.46 mg /mL for GCO20-AmB and GCO50-AmB samples respectively corresponding to 0.16 mg / mL and 0.11 mg / mL of solubilized AmB. It was not possible to obtain AmB solutions solubilized at these concentrations in water. Nanoparticles of the conjugates exhibited low polydispersity index and zeta potential negative profile and UV-Vis espectrum shows similar profile of the commercial formulation of the AmB solubilized with sodium desoxycholate (Fungizone®).